Pensamiento estratégico y cumplimiento de metas en la Municipalidad Provincial de Requena, 2023 - Pacaya Macuyama, Bety Maribel (2023)
The main objective of this research is to determine the relationship between strategic thinking and the fulfillment of goals in the Provincial Municipality of Requena, 2023. An applied methodology was applied, based on scientific theories related to strategic thinking and the fulfillment of objectives. The design adopted was non-experimental, because the variables were not intentionally manipulated. The study population comprised 245 workers, of which a sample of 150 was selected. The survey technique was used, with the questionnaire as the main instrument. The results indicate that the level of strategic thinking in the municipality is regular, with 29%. This is attributed, in part, to the fact that, although there is occasionally effective communication between areas, management tools are rarely applied to enhance performance and efficiency. On the other hand, the degree of compliance with goals is at an average level, with 46%, reflected in the partial achievement of actions such as disinfection or water treatment and the planning of municipal patrols by sectors in the district. In conclusion, a positive and significant correlation of 0.826 was identified between strategic thinking and goal achievement, with a significance of 0.000, which is lower than the p-worth 0f 0,01.